Essay in Exile and Exile From The Essay: Edward Said, Nuruddin Farah and Aleksandar Hemon (Ticontre. Teoria Testo Traduzione, 2018)
Although taking on always different nuances each time, the relationship between exile and essay writing in transnational contemporary literature in English is based on similar stylistic features and ideological positions.Edward Said describes some aspects of this relationship in his work – namely, in Reflections on Exile (2000) – while also reflecting on his own autobiographical experience as a Palestinian expatriate. In particular, he emphasizes that the essay author, as an intellectual, tackles the task to represent his original nation as well as those social groups and instances which are otherwise either forgotten or censored.Others, such as the Somali-born writer Nuruddin Farah, in Yesterday, Tomorrow. Voices from the Somali Diaspora (2000), and the Yugoslavian-born author Aleksandar Hemon, in The Book of My Lives (2013), further elaborate on this position, questioning their capacity to represent their communities both within the national borders and in exile. While sticking to some formal characteristics of the essay, however, their writing is also hybridized with autobiographical and other non-fictional elements to such an extent that they could be argued to experience ‘exile from the essay’ itself.In addition, Said, Farah and Hemon write while in exile from fragile nation-states or nations officially not existing anymore as such, thus being in a productive relationship with the transnational commitment of the contemporary intellectual proposed by Said himself in “The Public Role of Writers and Intellectuals” (2001) and other essays. Nel panorama transnazionale della produzione letteraria contemporanea in lingua inglese, la relazione tra la scrittura saggistica e la condizione di esilio dell’autore si presenta come un nesso fecondo, producendo, nel rispetto delle differenti peculiarità ravvisabili in ciascun caso, scelte stilistiche e posizionamenti ideologici analoghi.Edward Said descrive alcuni aspetti di questa relazione nella sua opera – in particolar modo, in Reflections on Exile (2000) – mettendo a fuoco, allo stesso tempo, la propria esperienza autobiografica di espatriato palestinese. Più specificamente, Said sottolinea il compito del saggista, in quanto intellettuale, di rappresentare la sua nazione d’origine e, al contempo, tutti quei gruppi e quelle istanze sociali che altrimenti risulterebbero dimenticate o censurate.Altri autori, come lo scrittore di origini somale Nuruddin Farah, in Yesterday, Tomorrow. Voices from the Somali Diaspora (2000), e l’autore, nato nella ex-Jugoslavia, Aleksandar Hemon, in The Book of My Lives (2013), hanno ulteriormente elaborato questo posizionamento, indagando a fondo la loro effettiva capacità di rappresentare le loro comunità di appartenenza, sia all’interno dei confini nazionali sia nella diaspora. Tuttavia, pur aderendo ad alcune caratteristiche formali del saggio, la loro scrittura risulta anche ibridata da alcuni elementi del genere autobiografico e di altri generi di non-fiction, al punto che la loro può essere definita anche come un’esperienza di “esilio dal saggio” stesso.Inoltre, tutti questi autori scrivono in una condizione di esilio da nazioni definite ‘fragili’ o che non esistono più, entrando così in una relazione produttiva con la portata transnazionale dell’impegno politico dell’intellettuale contemporaneo, proposto da Said in “The Public Role of Writers and Intellectuals” (2001) e in altri saggi. PAROLE CHIAVE:Saggio; esilio; fallimento della nazione; personal essay; Edward Said; Nuruddin Farah; Aleksandar Hemon; György Lukács.